EFFECT OF PALM EMPTY BUNCH ASH ON TRANSESTERIFICATION OF PALM OIL INTO BIODIESEL - Johan Sibarani; Syahrul Khairi; Yoeswono Yoeswono; Karna Wijaya; Iqmal Tahir (Indonesian Journal of Chemistry, 2007)
Biodiesel conversion from transesterification reaction palm oil with methanol was studied by using an ash of palm empty bunch as a base catalyst. Atomic absorption spectroscopy (AAS) and indicator titration analysis were used as tools for characterization of ash sample. Chemical structure of biodiesel was analyzed by GC-MS. The effects of ash sample weight (5, 10, 15, 20 and 25 g) immersed in 75 mL methanol and the methanol-palm oil mol ratio (3:1; 6:1; 9:1 and 12:1) toward the conversion of biodiesel were investigated. Biodiesel was prepared by refluxing palm oil and methanol containing ash sample. The reflux was done at room temperature for 2 h. Ester layer was distillated at 74 oC, extracted with aquadest and then dried using Na2SO4 anhydrous. The product was characterized by GC-MS, ASTM D 1298 (specific gravity 60/60 °F), ASTM D 97 (pour point), ASTM D 2500 (cloud point), ASTM D 93 (flash point), ASTM D 445 (kinematics viscosity 40 °C) and ASTM D 482 (ash content). The result of GC-MS analysis showed that methyl palmitate is primary content of biodiesel product. A 15 g weight of ash sample gave the maximum biodiesel conversion. By increasing methanol mole quantity, biodiesel conversion increased progressively and maximum at 9:1 methanol-palm oil ratio (84.12 %) and decreased on 12:1 ratio (75.58 %). Most of the biodiesel products were similar to those of the diesel physical characters.